Contribution of the immune system to bystander and non-targeted effects of ionizing radiation. Issue 1 (1st January 2015) - Rödel, Franz; Frey, Benjamin; Multhoff, Gabriele; Gaipl, Udo
Highlights X-irradiation displays anti-inflammatory activities if applied at low (< 1 Gy) doses. Pro-inflammatory effects and modulation of anti-tumour immune responses dominate at doses >2 Gy. Immune modulatory effects originate from nuclear damage and non-(DNA) targeted mechanisms. Abscopal effects of local X-irradiation are mediated by the induction of immunogenic forms of cell death. HSP70 immunotherapy may increases therapeutic effectiveness of (chemo) radiotherapy.